Optimization of N application for a maize crop grown in a shallow, irrigated soil - Díez López, J.A.; Tarquis, A.; Cartagena, M.C.; Vallejo, A. (Spanish Journal of Agricultural Research, 2006)
A method of evaluating net nitrogen (N) mineralization in shallow petrocalcic soils, based on N balances in non-fertilized plots, is proposed. During 1999, 2000 and 2001, estimated N mineralized in an irrigated maize crop (6.5 months) in Central Spain was: 73.3, 56.2 and 60.5 kg ha-1, respectively. The relationship between EUF-Norg (organic nitrogen extracted from soil by electroultrafiltration) and mean mineralized N, in this experiment during the three seasons, was 1 mg EUF-Norg 100 g-1 soil equivalent to 30 kg N ha-1. The calibration was applied to EUF-Norg values from soil samples analysed before sowing. These values, together with the mineral N, were used to estimate available N and consequently the optimal N rate. To evaluate the effect of N fertilizer rate on NO3 leaching and in N fertilizer-use efficiency (NFUE) three different rates of N were tested in 2000 and 2001: optimal N rate (NO), conventional N rate (NC) and a control no N (C). The NO rates for the maize crop were 150 and 130 kg N ha-1 in 2000 and 2001, respectively. Nitrogen losses of nitrate due to leaching were lower with NO than with the NC rate of 300 kg N ha-1. The NFUE values were higher for NO at 78.8% and 83.5% in 2000 and 2001, respectively than for NC at 48.7% and 49.3% in 2000 and 2001, respectively). However, in spite of the different levels of applied N, there was no difference in grain yield among treatments.